EARTH'S SEISMICITY AND SECULAR CHANGES OF ITS MAGNETIC FIELD - Orlyuk, M.; Marchenko, A.; Romenets, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Analysis of temporal changes in Earth's magnetic field and its seismicity for the period from 1950 to 2000 was performed. For the analysis the main magnetic field of the Earth ВIGRF–10 with a spherical harmonic to degree and order 13 was used, which allows us to study the characteristics of magnetic anomalies with dimensions in the first thousand kilometers. Temporal changes in the geomagnetic field for the period from 1950 to 2000 were divided into conditional long–wave "nuclear" and short "mantle–lithosphere" components. The planet, on the whole, showed a lower seismicity of south–western hemisphere, which is characterized by a significant reduction in "nuclear" part of the field, as compared with the north–eastern hemisphere. For the first time the connection between areas with high seismic activity and areas of positive growth "mantlelithosphere" component of the geomagnetic field was traced, which correspond to the zones of tectonic joints of lithospheric plates. The following two communication mechanisms: (a) the "temperature–magnetic", due to immersion of the magnetic blocks of the oceanic crust in a subduction zone, followed by a change in magnetization due to their warm–up; (b) "fluid–gas–magnetic", based on the formation and transformation of ferrous minerals under the influence of transmantle gases and fluids were proposed. Trans–mantle gases and fluids can play structures-formative role in relation to the modern geological and tectonic processes in the areas of joints of lithospheric plates.
Keywords: Earth's magnetic field; seismicity; lithospheric plates; magnetization; fluids